2005
DOI: 10.4218/etrij.05.0104.0086
|View full text |Cite
|
Sign up to set email alerts
|

Epipolar Geometry of Line Cameras Moving with Constant Velocity and Attitude

Abstract: Image resampling according to epipolar geometry is an important prerequisite for a variety of photogrammetric tasks. Established procedures for resampling frame images according to epipolar geometry are not suitable for scenes captured by line cameras. In this paper, the mathematical model describing epipolar lines in scenes captured by line cameras moving with constant velocity and attitude is established and analyzed. The choice of this trajectory is motivated by the fact that many line cameras can be assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Nevertheless, it is indicated that the epipolar curves of linear pushbroom satellite imagery hold two major geometric properties (Habib et al, 2004(Habib et al, , 2005. One refers to the Straightness Approximation: although the epipolar curves are in a quasihyperbola shape at infinity (see Eq.…”
Section: Epipolar Geometry Of Linear Pushbroom Imagerymentioning
confidence: 98%
“…Nevertheless, it is indicated that the epipolar curves of linear pushbroom satellite imagery hold two major geometric properties (Habib et al, 2004(Habib et al, , 2005. One refers to the Straightness Approximation: although the epipolar curves are in a quasihyperbola shape at infinity (see Eq.…”
Section: Epipolar Geometry Of Linear Pushbroom Imagerymentioning
confidence: 98%
“…Reconstruction of the geometry of an image at the time of imaging is the backbone of physical models. Two well-known approaches in this area encompass orbital parameters (Guichard 1983;Toutin 1986;Gugan 1986;Westin 1990;Radhadevi and Ramachandran 1994;2003;Valadan Zoej and Petrie 1998;Deltsidis and Ioannidis 2011) and multiple projection centers models (Kratky 1987;Orun and Natarajan 1994;Gupta and Hartley 1997;Kim 2000;Habib et al 2005). In the first case, the trajectory of the sensor is modeled based on Keplerian orbital parameters and time-dependent (temporal) polynomials are used to estimate attitude parameters.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…intersection of the epipolar plane, which contains the points O L and O R , and X, with the respective image plane. Summarizing, the epipolar geometry is described by two facts [10]. First, the corresponding point of a reference point in the left stereo partner can be found on a straight line in the right stereo image.…”
Section: Background On Epipolaritymentioning
confidence: 99%